2018
DOI: 10.36018/ijyr.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Yagya Therapy as supportive care in cancer patients improved quality of life: Case studies

Abstract: Cancer is becoming leading cause of death around the world. India has limited infrastructure and facility to fight the disease. In addition, side effects of current standard therapies like chemotherapy and radiation therapy severely hamper the quality of life (QOL) of patients. Alternative supportive therapies are a dire need, not only to reduce current therapeutic burden, but also to reduce the side effects, and deteriorating QOL of cancer patients. Yagya Therapy is an ancient Vedic therapeutic model, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…One of the important aspect of Yagya Therapy for getting improved pathological condition is the pulmonary inhalation of medicinal-smoke of the prescribed herbs (11)(12)(13)(14)(15)(16). As previously mentioned (9), pulmonary inhalation is an effective route to administer herbs, for various diseases, through the nasal route.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the important aspect of Yagya Therapy for getting improved pathological condition is the pulmonary inhalation of medicinal-smoke of the prescribed herbs (11)(12)(13)(14)(15)(16). As previously mentioned (9), pulmonary inhalation is an effective route to administer herbs, for various diseases, through the nasal route.…”
Section: Discussionmentioning
confidence: 98%
“…With regards to the present study, DAHH prescribed a hawan samagri for SCH treatment, which consists of more than 12 herbs (16). No metal was used in the herbal preparation.…”
Section: Herbal Mixture (Hawan Samagri) Preparationmentioning
confidence: 99%
“…Bheshaj Yagya translated here as Pharmacological Yagya processes are well delineated in prominent Ayurvedic texts as herb-infused fume therapy for humans and the rest of the environmental elements alike (3)(4)(5)(6)(7). The process of Yagya has been confirmed as therapy by Maharshi Charak as well (Charak Samhita 1/15/56) and Sushrut Samhita (Sushrut Samhita 1/1/5) (1).…”
Section: Introductionmentioning
confidence: 99%
“…Yagya is an ancient Indian therapeutic procedure (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), which is aimed at providing all round well-being of an individual. In the process of Yagya, coarse powder (hawan-samagri) made up of dry plantmedicines, as well as selected nutritious and aromatic substances, undergoes transformation into vapor phase, sublimation or decomposition by gradual heating; these phytomedicines spread along with the volatile substances and gases, released by the slow and controlled combustion process in Yagya fire (19).…”
Section: Introductionmentioning
confidence: 99%
“…The effects were tested by sequential readings on different clinical physiological, microbiological, hematological, biochemical and pathological parameters, and the results showed encouraging healing possibilities of Yagyopathy for pulmonary tuberculosis (15)(16)(17)19,21). Batham (27) showed that Yagya Therapy, as supportive care, improved quality of life in cancer patients.…”
Section: Introductionmentioning
confidence: 99%